Projeto de vida ético: um estudo sobre contribuições para a construção de projetos de jovens do ensino médio - Schwarz, Karin (2022)
The aim of this work is to explore contributions that reflection on values and on work brings to the building up of ethical life projects addressed to the youth. Initially, we approached two concepts considered as basic: “life project” and “ethical life project”. It was necessary to develop important discussions regarding the right to a life project and the impacts of social reality on their elaboration and concretization. During this study, the focus lies on the dimension of work, since it is present in the approach that guides this study, a main category in man’s life, a starting point and the presupposition of humanization. The ethical life project is the one focused on the collectivity, guided by the search of common good and it is critical about social reality. Therefore, the necessary changes in reality will be possible through work and the questioning of values on which its relations are grounded in the theoretical-methodological referential of this research is Social-Historic Psychology. To carry it on, two female subjects were interviewed, a 17 and a 15 year old, both High School students, one from a public school and the other from a private school. An activity was proposed for them to reflect on what they understood as work, on what their personal values are, and if (and how) these relate. The analysis took place in two distinct moments, an individual analysis of each subject’s answers, and then by articulating both subjects’ answers, aimed at identifying the contributions that the activity provided them, so that a dialogue about the main aspects that emerged could be established. The conclusion allows us to understand that these reflections are important to the development of a critical consciousness regarding thinking the future, particularly when referring to work and profession and must overcome alienated views. However, these same reflections also allowed us to understand that reflections should permeate school spaces and not be restricted only to specific spaces. Education has to be understood, therefore, as a broad process which allows and encourages reflection on aspects of life, especially on values, work and on projects for the future centered in ethical development